Administrative and legal tools of the Ministry of Internal Affairs service centers interaction with other law enforcement agencies - О. V. Dzhafarova; О. V. Shatrava (Law and Safety)
Attention is focused on revealing the content of the new service ideology of service centers of the Ministry of Internal Affairs and law enforcement agencies, aimed at ensuring the rights and freedoms of people and citizens, as well as the interests of legal entities during the provision of high-quality public services in the field of road safety.